2022
DOI: 10.24198/jmpp.v6i1.25069
|View full text |Cite
|
Sign up to set email alerts
|

How South Africa Governing Their Services Contract in Public Private Partnership: A Systemic Review Study

Abstract: Governance is very important in the commitment to continue cooperation in the public-private partnership (PPP). By using the literature study method, this research tries to explain the forms of partnerships that exist in the South African country. Based on research with the theme of PPP in the South African country. Based on the information gathered in this article, there are 3 issues found in PPP in South Africa: health, food security, and public services. This study also explains the variables that exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In addition, research conducted by (Rifqi Abdul Hafidh 2022) concluded that policy evaluation is an activity carried out to assess performance and benefits and policies. In addition, it is also carried out to measure the gap that exists between the expectations that are expected to be achieved with the facts that actually occur in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research conducted by (Rifqi Abdul Hafidh 2022) concluded that policy evaluation is an activity carried out to assess performance and benefits and policies. In addition, it is also carried out to measure the gap that exists between the expectations that are expected to be achieved with the facts that actually occur in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the future, it is hoped that this review will be able to provide an overview of the essential requirement to improve recording management to improve public services. For example, service contracts in publicprivate partnerships (Hafidh, 2022), or (motor) vehicle tax services (e-Samsat services) (Priastuti et al, 2022). This study also could help to ensure compliance, enhance decision-making, improve operational efficiency, preserve institutional memory, and deliver satisfactory services to citizens.…”
Section: Introductionmentioning
confidence: 99%